Anemia - A simple community based diagnostic tool - Niraj Pandit; Rajesh Mehta (Indian Association of Preventive and Social Medicine, 2010)
Anemia is the most common morbidity worldwide. World Health Organization has defined anemia as "a condition in which the hemoglobin content of blood is lower than normal as a result of deficiency of one or more essential nutrients regardless of the cause of such deficiency". Hemoglobin is necessary for transporting oxygen from the lungs to other tissues and organs of the body. ......